Pengembangan Media Audiovisual untuk Pembelajaran Memperbaiki komputer di SMK - Sutikno Aminah; Syamsurizal Syamsurizal; Syaiful Syaiful (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2015)
Learning process for repairing computer competency at skill competency of Multimedia at SMK Negeri 2 Merangin has not been run effectively. In fact, learning material in repairing computer just used modul as teaching materi and media learning. While, to get the competency thad needed, learning process should be supported by leaning tool well. For answer the problem above, teacher as a fasilitator in achievment of students competency is demanded to creative in learning management. One of them is by finding alternative solution that is by develop audiovisual media for learning of Repairing Computer that can give solution in lerning process. Development of this media aim to product efective media in learning material of repairing computer at SMK Negeri 2 Merangin. Development model that chosen is based on Borg and Gall model that adapted lerning design Dick and Carey model. Development process is done by 5 main steps: (1) Doing analysis, (2) Design pre product, (3) Validation and revision, (4) Try out at small scale field and, (5) Try out big group field.